2013
DOI: 10.4067/s0718-95162013005000032
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of potassium sulphate on the growth and chemical composition of wheat (Triticum aestivum L.) in salt-affected soils

Abstract: Potassium (K) and sodium (Na) coexist on the soil exchange complex and soil solution. Both cations may exert antagonistic or synergistic effects on mutual absorption and translocation within plants, particularly under saline and saline-sodic field conditions. This study investigated the role of K in alleviating the adverse effects of Na on wheat [Triticum aestivum (L), Iquilab-91] grown at two fields sites varying in salinity. The soils were moderately calcareous, weakly structured, mixed hyperthermic Typic Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
2
20
0
4
Order By: Relevance
“…The fertilizers showed positive effect on growth and development under salinity conditions. Similar results were reported that growth of rice and wheat crop increased significantly in response to application of potash under stress conditions (Hussain et al, 2013). It may be due to increase rate of photosynthesis as depicted that the rate of photosynthesis becomes enhanced by the application of potassium in stressed environment (Ali et al, 1999).…”
Section: Phosphorous Contents Of Roots and Shoots (Mg/g Dry Wt)supporting
confidence: 77%
See 1 more Smart Citation
“…The fertilizers showed positive effect on growth and development under salinity conditions. Similar results were reported that growth of rice and wheat crop increased significantly in response to application of potash under stress conditions (Hussain et al, 2013). It may be due to increase rate of photosynthesis as depicted that the rate of photosynthesis becomes enhanced by the application of potassium in stressed environment (Ali et al, 1999).…”
Section: Phosphorous Contents Of Roots and Shoots (Mg/g Dry Wt)supporting
confidence: 77%
“…Potassium is macronutrients that used in the form of sulphate of potash (SOP) as K 2 SO 4 Under stressful environment, addition of potash fertilizers increased the growth and yield (Hussain et al, 2013). In present study, potassium was applied to alleviate the adverse effect of salinity and there was significant increase in lengths, fresh and dry weights of shoots and roots in both genotypes.…”
Section: Phosphorous Contents Of Roots and Shoots (Mg/g Dry Wt)mentioning
confidence: 87%
“…In the present study, potassium sulphate was used to alleviate the negative effects of salt stress and an improvement in plant height, fresh and dry weights was recorded in both wheat cultivars. Positive influence of potassium on plant growth and productivity under saline environments has been reported by Rashid et al (2001) and Hussain et al (2013) as well. Indirect evidences are also available indicating that potassium and sulphate have central role in the construction of some important proteins (Khan et al, 2008;Khan et al, 2010), which are necessary to impart stress tolerance in plants ( Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 81%
“…Development of plant depends particularly on the accessibility of appropriate amounts of potassium fertilizer (Kausar and Gull, 2014b), which improves plant growth and productivity (Hussain et al, 2013, Saffa et al, 2013 especially in the plants facing salt stress. These findings too are in accordance with those of Ashraf et al (2003Ashraf et al ( , 2015, and Kausar et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increasing in Na + concentration will reduce the absorption of essential ions such as K (Gupta and Huang 2014). Thereby K fertilization under saline condition is suitable (Schachtman and Liu 1999;Garg and Gupta 1998;Sherif et al, 1998;Hussain and Khattak 2005;Cakmak 2010;Hussain et al, 2013;Kausar and Gull 2014).…”
Section: Methodsmentioning
confidence: 99%